Organic dye anchor peptide conjugates as an advanced coloring agent for polypropylene yarn. Issue 1 (January 2021) - Zimmermann, Marc; Stomps, Benjamin; Schulte-Osseili, Christine; Grigoriev, Dmitry; Ewen, Dirk; Morgan, Andrew; Böker, Alexander
Polypropylene as one of the world's top commodity polymers is also widely used in the textile industry. However, its non-polar nature and partially crystalline structure significantly complicate the process of industrial coloring of polypropylene. Currently, textiles made of polypropylene or with a significant proportion of polypropylene are dyed under quite harsh conditions, including the use of high pressures and temperatures, which makes this process energy intensive. This research presents a three-step synthesis of coloring agents, capable of adhering onto synthetic polypropylene yarns without harsh energy-consuming conditions. This is possible by encapsulation of organic pigments using trimethoxyphenylsilane, introduction of surface double bonds via modification of the silica shell with trimethoxysilylpropylmethacrylate and final attachment of highly adhesive anchor peptides using thiol-ene chemistry. We demonstrate the applicability of this approach by dyeing polypropylene yarns in a simple process under ambient conditions after giving a step-by-step guide for the synthesis of these new dyeing agents. Finally, the successful dyeing of the yarns is visualized, and its practicability is discussed.